Effect of low temperatures on the selection by tolerance for hybrid progenies of potato (Solanum sp.) with introgression of Solanum commersonii., in the community of Occopata, Cusco - Zarate Aller, Evelin (2023)
Frost tolerance represents an important factor in rural high Andean communities, where native potatoes are their main source of food, and many of which are adapted to low temperatures, as well as wild potato species, that can confer greater adaptation to frost. The object of investigation was to select the progenies with introgression of Solanum commersonii., that present tolerance to frost, and have good agronomic characteristics, under the conditions of the community of Occopata, district of Santiago, Cusco. The methodology consisted of evaluating the progenies under study during three agricultural campaigns, in an area that frequently presents frosts. The degree of damage affected by frost, the level of recovery and the yield at the end of the vegetative period were evaluated. From the results obtained in the first agricultural campaign, the progeny “Superior Haploid + cmm fus” was the most affected by frost, reaching a degree of damage of 75% of damage to the foliage, while for the second campaign, it was determined that the progeny “Puno III gen (Puno cold breed)”, reached a degree of damage in 50% of affected leaves. The progenies “cb adg 21 x cmm fus” and “cb adg 13 x cmm fus” had the best level of recovery potential and average growth. Meanwhile, the yield was higher in the progeny “cb adg 21 x cmm fus”, with an average of 22 t/ha, for the third campaign.